Symptoms, Mental Health, and Quality of Life Among Patients After COVID-19 Infection: A Cross-sectional Study in Vietnam - Hai Nguyen Thanh; Duc Cap Minh; Hien Hoang Thu; Duc Nguyen Quang (Korean Society for Preventive Medicine, 2024)
Objectives: This study was conducted to characterize the symptoms, mental health, quality of life (QoL), and associated factors following the coronavirus disease 2019 (COVID-19) infection. Methods: This cross-sectional study included 394 participants previously infected with COVID-19 in Ho Chi Minh City, Vietnam. Mental health was assessed using the 21-item Depression, Anxiety, and Stress Scale (DASS-21). Participants self-reported health-related QoL was measured with the EuroQol 5-Dimension 5-Level (EQ-5D-5L) scale. Results: Among the participants, 76.4% reported experiencing at least one symptom following COVID-19 infection. The most common symptoms were fatigue (42.1%), cognitive dysfunction (42.9%), and hair loss (27.9%). According to the DASS-21 results, the proportions of depression, anxiety, and stress were 28.7%, 26.4%, and 20.6%, respectively. The mean scores on the EQ-5D-5L and the EuroQol Visual Analog Scale were 0.94±0.11 and 84.20±13.11, respectively. Regarding QoL issues, the highest proportion of participants (32.7%) reported experiencing anxiety or depression, followed by pain or discomfort (25.4%). Multivariable logistic regression analysis revealed that factors associated with the presence of symptoms following COVID-19 infection included female (odds ratio [OR], 2.84; 95% confidence interval [CI], 1.65 to 4.91) and having QoL issues (OR, 3.25; 95% CI, 1.71 to 6.19). Conclusions: The study investigated the prevalence rates of various symptoms following COVID-19 infection. These findings underscore the need to prioritize comprehensive care for individuals recovering from COVID-19 and to implement strategies to mitigate the long-term impact of the disease on mental health and QoL.